All near-infrared multiparametric luminescence thermometry using Er3+, Yb3+-doped YAG nanoparticles. Issue 26 (29th April 2021) - Periša, Jovana; Ristić, Zoran; Piotrowski, Wojciech; Antić, Željka; Marciniak, Lukasz; Dramićanin, Miroslav D.
Abstract : Four completely new NIR luminescence temperature readouts in the second and third biological windows are demonstrated with YAG:Er 3+, Yb 3+ nanoparticles. Abstract : This paper presents four new temperature readout approaches to luminescence nanothermometry in spectral regions of biological transparency demonstrated on Yb 3+ /Er 3+ -doped yttrium aluminum garnet nanoparticles. Under the 10 638 cm −1 excitation, down-shifting near infrared emissions (>10 000 cm −1 ) are identified as those originating from Yb 3+ ions' 2 F5/2 → 2 F7/2 (∼9709 cm −1 ) and Er 3+ ions' 4 I13/2 → 4 I15/2 (∼6494 cm −1 ) electronic transitions and used for 4 conceptually different luminescence thermometry approaches. Observed variations in luminescence parameters with temperature offered an exceptional base for studying multiparametric temperature readouts. These include the temperature-dependence of: (i) intensity ratio between emissions from Stark components of Er 3+ 4 I13/2 level; (ii) intensity ratio between emissions of Yb 3+ ( 2 F5/2 → 2 F7/2 transition) and Er 3+ ( 4 I13/2 → 4 I15/2 transition); (iii) band shift and bandwidth and (iv) lifetime of the Yb 3+ emission ( 2 F5/2 → 2 F7/2 transition) with maximal sensitivities of 1% K −1, 0.8% K −1, 0.09 cm −1 K −1, 0.46% K −1 and 0.86% K −1, respectively. The multimodal temperature readout provided by this material enables its application in different luminescence thermometry setups as well as improved the reliability of the temperature sensing by the cross-validation between measurements.